2021
DOI: 10.3390/w13182574
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Age Performance Assessment in Distribution Networks

Abstract: Water age is frequently used as a surrogate for water quality in distribution networks and is often included in modelling and optimisation studies, though there are no reference values or standard performance functions for assessing the network behaviour regarding water age. This paper presents a novel methodology for obtaining enhanced system-specific water age performance assessment functions, tailored for each distribution network. The methodology is based on the establishment of relationships between the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In previous studies on water distribution systems, researchers created "performance indexes" where they correlated water age to an index that reflected one or more water quality parameters. [24][25][26][27] Several studies found that, at around 10 hours, there was a sharp decrease in water quality, 24,25,27 though this depended on the temperature and the distribution system layout, and initial water quality. With similar indexes for specific premise plumbing systems, the water age could be more directly linked to the quality.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on water distribution systems, researchers created "performance indexes" where they correlated water age to an index that reflected one or more water quality parameters. [24][25][26][27] Several studies found that, at around 10 hours, there was a sharp decrease in water quality, 24,25,27 though this depended on the temperature and the distribution system layout, and initial water quality. With similar indexes for specific premise plumbing systems, the water age could be more directly linked to the quality.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
“…This is especially true for microbial quality, where the quality remains high while the chlorine residual persists and water temperatures are unfavorable for growth (low or high), but can rapidly decline once chlorine dissipates and temperatures become favorable. [24][25][26][27] Given this rapid decline in quality, the average water age may not reflect the average water quality. Therefore, a statistical approach maybe more valuable than exploring average flows.…”
Section: Introductionmentioning
confidence: 99%
“…They found similar trends with higher initial chlorine concentrations leading to a higher percentage of nodes above a certain concentration of chlorine. Past research has also found the chlorine supply to the service line to be very low or nondetect at times . Overall, the trends remained the same for the influent chlorine concentrations, with the purging decreasing the amount of time a fixture spent with low chlorine, especially for the shower.…”
Section: Resultsmentioning
confidence: 76%
“…Zhang and Edwards found higher chlorine decay in metallic pipes that corrode at high rates, such as cast-iron, galvanized-iron, copper, and old lead pipes than in relatively inert pipes, such as plastic, glass, and stainless steel pipes. If the temperature is higher, chlorine decays faster. The overall free chlorine decay also depends on the TOC in the water and the pH, with lower pH and TOC values leading to more effective disinfection, though lower pH can lead to pipe corrosion, which, in turn, can affect the k w . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation